Authentic leadership and organizational citizenship behavior through the mediating effect of employee engagement and organizational commitmnet in pharmaceutical companies in Jordan - Ayoub, Sead Assad Abdul Kareem (My University, 2023)
Bu çalışmanın amacı, çalışan bağlılığı (CB) ve örgütsel bağlılık (ÖB) etkilerinin, otantik liderlik (OL) ile örgütsel vatandaşlık davranışı (ÖVD) arasındaki ilişki üzerindeki etkisini araştırmaktır. Daha önceki çalışmalar liderlik tarzları ile örgütsel vatandaşlık davranışı arasındaki ilişkiyi ve etkilerini incelemiştir. Ancak biz, otantik liderliğin kullanımı ile ÖVD arasındaki ilişkinin diğer faktörler aracılığıyla nasıl etkilenebileceğine ve aracılık rollerine özellikle odaklanıyoruz. Bu araştırma, Ürdün ilaç endüstrisinde gerçekleştirilmiştir. Bu sektörün seçilmesindeki ana nedenlerden biri, COVID-19 döneminde özellikle hayat kurtarma konusunda yüksek önemini ve katkısını gösteren sağlık hizmetleri alanını iyileştirmeyi amaçlamamızdır. Ayrıca, ilaç endüstrisi, Ürdün GSYİH'sına çok yüksek katkıda bulunarak ekonomik açıdan büyük öneme sahiptir. Ürdün ilaç endüstrisinde çalışan 253 kişilik bir örnek, 2200 çalışana doğrudan LinkedIn aracılığıyla ve gözlem ziyaretleri yoluyla gönderilen bir anket yoluyla toplanmıştır. Çalışmanın bulguları, OL'nin ÖVD üzerinde anlamlı bir etkisi olduğunu ve CB'nin bu ilişkide tam aracılık ettiğini göstermektedir. Öte yandan, ÖB, OL ve ÖVD arasındaki ilişkide kısmi olarak aracılık yapmaktadır.

The purpose of this study is to investigate the impact of employee engagement (EE) and organizational commitment (OC) on the relationship between authentic leadership (AL) and organizational citizenship behavior (OCB). Earlier studies conducted the relationship and effects of leadership styles and organizational citizenship behavior. However, we are focusing on how the relationship between the usage of authentic leadership and OCB can be affected and mediated through other factors. This is done by examining the mediating roles that organizational commitment and employee engagement play in this relationship. The research of this study is conducted in pharmaceutical industries of Jordan. The main reasons after choosing this sector are that we are aiming to improve health care fields in Jordan as it showed its high importance and contributing in saving lives especially in COVID-19 era. Also, pharmaceutical industry ranks second in terms of economic importance in Jordan with a very high contribution of Jordan’s GDP. A sample of 253 employees working in pharmaceutical industries in Jordan were collected through a questionnaire that was sent to 2200 employees, directly through LinkedIn, and through sight visits in order to collect the desired number of respondents. The findings of the study showed that there is a significant impact of authentic leadership on OCB, and that EE fully mediates the relationship between AL and OCB. On the other hand, OC partially mediates the relationship between AL and OCB.
Keywords: Authentic leadership (AL); Çalışan bağlılığı (EE); Employee engagement (EE); Employee motivation; İlaç şirketleri; İşçi güdülemesi; Leadership; Liderlik; Organizational behavior; Organizational citizenship behavior (OCB); Organizational commitment; Organizational commitment (OC); Otantik liderlik (AL); Örgütsel bağlılık; Örgütsel bağlılık (OC); Örgütsel davranış; Örgütsel vatandaşlık davranışı (ÖVD); Pharmaceutical companies